ANALISIS URGENSI PENATAAN WILAYAH PERTAHANAN INDONESIA DALAM MENGHADAPI ANCAMAN NON-TRADISIONAL DI RUPAT UTARA (STUDI KASUS: PENYELUNDUPAN NARKOTIKA) - Mabruri, Agil Fadlan; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research analyzes the Urgency of Arranging Indonesia's Defense Area in Facing Non-Traditional Threats in North Rupat in a case study of narcotics smuggling in the 2019-2022 period. The North Rupat area is a sub-district located on Rupat Island, Bengkalis Regency, Riau, which is the border area between Indonesia and Malaysia. North Rupat faces directly the Malacca Strait, which makes it an area vulnerable to both traditional and non-traditional threats. Narcotics smuggling is a non-traditional threat to state security as an actual threat that is currently occurring in North Rupat. North Rupat is a very strategic location for international narcotics syndicates to supply narcotics and distribute narcotics in Indonesia. This research was carried out descriptive qualitative using several methods for collecting data, including interviews, observations, and literature studies from books, journals, websites, and documents related to this collaboration. This research uses a constructivist perspective and securitization theory. The results of this article show how in accordance with securitization theory, it is necessary to escalate the issue of narcotics smuggling into a threat to state security that needs to be taken seriously by both the government and society. Then, in an effort to prevent and handle narcotics smuggling, there is an urgency to organize defense areas as regulated in Government Regulation no. 68 of 2014 concerning Defense Area Arrangement so that the national defense implementation agenda can be carried out optimally and effectively. Keywords: Dynamics, Defense Area Arrangement, Securitization, Law Enforcement Officials, North Rupat, Riau, Non-traditional Threats.